Preface: 3rd International Conference on Theoretical Physics, Computers and Electronic Engineering (TPCEE 2024) - Kennan, Malcolm; Yue, Qianjiang (Transactions on Computer Science and Intelligent Systems Research, 2024)
This volume contains papers accepted by the 2024 3rd International Conference on Theoretical Physics, Computers and Electronic Engineering (TPCEE 2024), which was held at Toronto, Canada during October 19-20, 2024. TPCEE 2024 brought together innovative scholars and industry experts to jointly hold a forum. The main objective of the conference is to promote the research and development activities of theoretical physics, astrophysics, quantum physics, computer engineering, information technology, and electronic engineering. The other objective is to promote the exchange of scientific information among researchers, developers, engineers, students, and practitioners around the world. Over 70 participants from many countries attended this conference, which included 4 keynote speeches and 24 oral presentations on different aspects in 4 sections. The cutting-edge research works were presented by such renowned keynote speakers. The TPCEE 2024 was a success where all the participants gathered on this platform and share experiences and research findings in their respective fields. Organizing Committees of TPCEE 2024 Toronto, Canada